Basic Elements of Project Management on the Example of Lean Manufacturing Student Research Group Activities - Katarzyna Styk; Klaudia Drobek (Journal of Management Practices, Humanities and Social Sciences, 2019)
The aim of this paper is to present the author's approach to project management. It was developed in view of the growing popularity of this methodology in the world of business and manufacturing. The current approach has been developed on the basis of methodologies such as Prince2, PMI Book, Demimnga Cycle and Product Life Cycle. Individual elements necessary to launch the project were selected and presented in the form of project documentation. It's part of project charter, organisational structure, division of labour structure, project schedule, project budget, project status report. For all documents, a customised layout of content, developed in accordance with the above mentioned methodologies, has been developed. The developed methodology was implemented into the project of building a training production line under the name “AGH Lean Line”, carried out by the student research group “Management” operating at the AGH University of Science and Technology in Krakow.